Pengaruh Layanan Guru Bimbingan dan Konseling terhadap Pembentukan Karakter Siswa di SMP Takhasus Al-Qur’an - Muhammad Zidan Dermawan; Sri Haryanto; Muhammad Saefullah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to explore how guidance and counseling services at SMP Takhasus Al-Qur’an are implemented, their influence on students’ character development, as well as the supporting and inhibiting factors in this process. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The findings reveal that guidance and counseling services are carried out effectively and positively affect students’ discipline, responsibility, religiosity, and independence. Supporting factors include the professional competence of guidance counselors, parental support, and the school’s religious environment. Inhibiting factors consist of limited facilities, low student motivation, and negative influences from outside the school environment. Therefore, guidance and counseling services play a significant role in fostering students’ Islamic character development.